Vpliv dolgotrajnega antikoagulacijskega zdravljenja na fibrinolitično aktivnost krvi pri bolnikih z vensko trombozo - Majal, Maja (Medicinski razgledi, 2000)
Ninety-nine consecutive patients (42 M, 57 W) with objectively confirmed deep vein thrombosis (DVT) were included. They were 60 +- 10 years old. Fourty-seven were older than 65 years. In 41 patients DVT was idiopathic. In 20 patients advanced malignancy was present. In other patients DVT developed after surgery or immobilization. In acute DVT patients were treated five to seven days with standard heparin combined with warfarin after one to three days of heparin treatment. The prothrombin time, fibrinogen, D-dimer and euglobulin clot lysis time (ECLT) were determined on the first and the seventhday of treatment and three and six months after the acute DVT: For the same anticoagulant effect patients older than 65 years needed a lower doses ofwarfarin than younger patients. During a long-termtreatament with warfarin 47% of the INR in patients without malignancy and only 25% of INR in patients with malignancy were in the therapeutic range (INR 2.0-3.0). Three months after acute DVT significant prolongation of ECLT was observed. The concentration of D-dimers and fibrinogen decreased in the first three months. Six months after the acute DVT the results were similar to those obtained after three months. During the warfarin tretament we observed prolongation of ECLT and values were back to normal after finishing the warfarin therapy. Therefore, we assume that a long-term warfarin treatment influenced blood fibrinolytic activity.
Keywords: Thrombophlebitis; venska tromboza; Drug therapy; therapy; zdravljenje; zdravila; Anticoagulants; drug; Blood coagulation tests; krvna koagulacija; Middle age; Aged; Neoplasms; Immobilization; Heparin; Warfarin; Prothrombin time; Fibrinogen; Treatment outcome